ANALISA KUALITAS KINERJA USAHA BERDASARKAN ORIENTASI KEWIRAUSAHAAN DAN STRATEGI BISNIS - Purnomo, Purnomo (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2021)
Judging from the cycle of business development in Indonesia, fashion is one of the business sectors that has contributed a lot in providing business opportunities for entrepreneurs. The lack of courage of usasha actors in taking risks has hampered the development of the business itself. This analysis aims to determine the quality of business performance based on entrepreneurial orientation and business strategy. The method in this research is to take samples randomly using the Slovin formula as many as 90 respondents. The analytical method used is descriptive analysis and verification which consists of the classical assumption test of multiple regression analysis. The results of the research based on verification analysis show that business strategy partially has a significant effect on business performance and entrepreneurial orientation and simultaneously affects business performance and descriptive analysis states that the respondent's response is good enough for business strategy and entrepreneurial orientation, which indicates a good response of respondents to performance. their business, and for entrepreneurial orientation partially significant effect on business performance. The author's advice to business people in the fashion industry is to consider more in the search for new opportunities and challenges by making risks a challenge in achieving the goals to be achieved. Keywords: Entrepreneurial Orientation, Business Strategy, Business Performance.